Synopsis: Commercialization and dietary diversity of Rwandan smallholder farmers: a focus on women and youth headed households - Mukangabo, Emerence; Warner, James (International Food Policy Research Institute, 2025)
In the last two decades, the government of Rwanda has significantly lowered stunting among children under five years from 48% in 2000 to 33% in 2020 and recognizes dietary diversity as one the approaches to overcome malnutrition and micronutrient deficiencies. A key priority of the Second National Strategy for Transformation (NST2) is to tackle malnutrition and to reduce stunting rates among children. Therefore, using a household dietary diversity score as a proxy for household access to nutritious foods, this policy note outlines how commercialization impacts dietary diversity, with a focus on women and youth headed households. Key findings include: The rural smallholder farmers diet is predominantly based on cereals, roots and tubers as well as vegetables. Even when controlling for relevant variables, women do not have more diverse consumption patterns, however, they do, relative to male headed households, consume more diverse foods the greater their level of commercialization. Despite an overall lack of resources and income, youth-headed households show a positive relationship with household dietary diversity when compared to mature-headed households. Determinants that positively influence household dietary diversity include the level of commercialization, household non-farm assets, market access, education of the household head, the presence of children under five in the household, irrigation, land size, and livestock holdings.